Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s10236-022-01525-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale eddy variability in the Caribbean Sea

Abstract: The spatial distribution, and the monthly and seasonal variability of mesoscale eddy observations derived from the AVISO eddy atlas are assessed in the Caribbean Sea during 1993–2019. The average lifetime for the whole set of eddies is 62 ± 37 days, mean amplitude of 7 ± 4 cm for cyclonic and 7 ± 4 cm for anticyclonic and mean radius of 100 ± 31 km for cyclonic and 108 ± 32 km for anticyclonic. Cyclonic eddies are on average more nonlinear than anticyclonic ones. The spatio-temporal variability in the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Recently, based on 27 years of satellite altimetry data, López‐Álzate et al. (2022) identified that the average lifetime for all the eddies in the Caribbean Sea is 62 ± 37 days (mean ± standard deviation) and most of them (∼90%) have a lifetime shorter than 160 days. Therefore, a period shorter than 160 days appears to be an appropriate choice for the cut‐off period of the mesoscale window.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, based on 27 years of satellite altimetry data, López‐Álzate et al. (2022) identified that the average lifetime for all the eddies in the Caribbean Sea is 62 ± 37 days (mean ± standard deviation) and most of them (∼90%) have a lifetime shorter than 160 days. Therefore, a period shorter than 160 days appears to be an appropriate choice for the cut‐off period of the mesoscale window.…”
Section: Methodsmentioning
confidence: 99%
“…The mean circulation in the Caribbean Sea is characterized by currents from the Lesser Antilles to the Yucatan Channel and into the GoM (Gordon, 1967; Johns et al., 2002) and is a major pathway for transporting mass, heat, salt, and other tracers in the Atlantic Circulation System. Mesoscale eddies are also ubiquitous in the Caribbean Sea (Centurioni & Niiler, 2003; Jouanno et al., 2012; López‐Álzate et al., 2022; Pratt & Maul, 2000; van der Boog et al., 2019a, 2019b). These eddies advect cold filaments, modulate heat balance in the interior of the Caribbean Sea, and affect the temperature variability through the upwelling in the Cariaco Basin (Astor et al., 2003; Jouanno & Sheinbaum, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOMs are a statistical tool used to compress the information contained in a large amount of data into one single set of maps (Kohonen, 1982), reducing the high-dimensional feature space of input data to a lower-dimensional network of units called neurons. SOM analysis has been used in the oceanography context in several studies (Liu et al, 2006;Hernández-Carrasco and Orfila, 2018;López et al, 2022). Learning processes are carried out by an interactive presentation of the input data to a preselected neuronal network, which is modified during the iterative process.…”
Section: Methodsmentioning
confidence: 99%
“…The Caribbean Sea, located between 9°N -21°N and 88°W-60°W , is a semi enclosed basin bordered by the Lesser Antilles at the east, the Greater Antilles at the north, the eastern portion of Central America at the west and the northern coasts of South America at the south (Figure 1). The wave dynamic in the basin is mainly controlled by the westward surface trade winds, which show a large seasonality, and a low-level wind core with higher speeds that gives origin to the Caribbean Low Level Jet (CLLJ) with a kernel located at the center of the basin (Poveda et al, 2006;Orfila et al, 2021;Loṕez-A ́lzate et al, 2022). Wind seasonality is associated with the meridional migration of the Inter Tropical Convergence Zone (ITCZ), which is also responsible for the path and penetration of transient features as cold fronts and tropical storms.…”
Section: Study Site: the Caribbean Basinmentioning
confidence: 99%